2016
DOI: 10.1016/j.biomaterials.2016.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticulate mineralized collagen scaffolds induce in vivo bone regeneration independent of progenitor cell loading or exogenous growth factor stimulation

Abstract: Current strategies for skeletal regeneration often require co-delivery of scaffold technologies, growth factors, and cellular material. However, isolation and expansion of stem cells can be time consuming, costly, and requires an additional procedure for harvest. Further, the introduction of supraphysiologic doses of growth factors may result in untoward clinical side effects, warranting pursuit of alternative methods for stimulating osteogenesis. In this work, we describe a nanoparticulate mineralized collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
95
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 50 publications
5
95
0
3
Order By: Relevance
“…In comparison to non-mineralized collagen glycosaminoglycan scaffolds, MC-GAG has an increased stiffness and the ability to release calcium and phosphate ions from the scaffold into culture, which may be contributors to the osteogenic capabilities [17, 25] . Although we have shown that MC-GAG induces osteogenesis efficiently in the absence of BMP-2 [15, 22] , BMP-9 has been demonstrated to be the most osteogenic BMP family member in both in vitro and in vivo ectopic mineralization studies using C3H10T1/2 cells and C2C12 cells [3, 26] . Thus, a comparison between scaffold-mediated and scaffold/growth factor-mediated osteogenesis was important to understand whether additional modifications of the scaffold could be performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to non-mineralized collagen glycosaminoglycan scaffolds, MC-GAG has an increased stiffness and the ability to release calcium and phosphate ions from the scaffold into culture, which may be contributors to the osteogenic capabilities [17, 25] . Although we have shown that MC-GAG induces osteogenesis efficiently in the absence of BMP-2 [15, 22] , BMP-9 has been demonstrated to be the most osteogenic BMP family member in both in vitro and in vivo ectopic mineralization studies using C3H10T1/2 cells and C2C12 cells [3, 26] . Thus, a comparison between scaffold-mediated and scaffold/growth factor-mediated osteogenesis was important to understand whether additional modifications of the scaffold could be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we sought to gain an understanding of whether additive effects of endochondral and intramembranous ossification would occur. Lastly, BMP-2 and MC-GAG both stimulate hMSC differentiation primarily via the canonical, Smad1/5 dependent BMPR signaling pathway [15, 22] . However, several investigators have demonstrated differences in BMP-9 signalling including receptor affinity [27] .…”
Section: Discussionmentioning
confidence: 99%
“…18 Mineralized collagen scaffolds induced bone regeneration of criticalsized defects in vivo without addition of exogenous growth factors. 19 Thus, it is envisaged that osteogenesis will be promoted by the controlled delivery of polymer-stabilized ACP in a bioactive form that can be readily utilized for collagen biomineralization.…”
mentioning
confidence: 99%
“…Although carbonated hydroxyapatite is known to be the major type of calcium phosphate in bone ECM, it is difficult to speculate on whether this is necessary or appropriate for stimulating regeneration as excellent osteogenic differentiation has been reported in scaffolds with brushite as the primary calcium phosphate component. [2,7,9,11,98] Furthermore, the significance of the less abundant inorganic ions such as silicon and magnesium are also incompletely described for regeneration.…”
Section: Challenges In Development Of Biomimetic Scaffoldsmentioning
confidence: 99%
“…Our group has reported similar results in the osteogenic mechanism of Col-GAG scaffolds with the upregulation of phosphorylated ERK1/2 during osteogenic differentiation. [2,98] Recently, we have also tested the PD98059 small molecule MEK inhibitor on hMSC differentiation on CG scaffolds and noted inhibition of osteogenesis and matrix mineralization (JCL, unpublished observations).…”
Section: Challenges In Development Of Biomimetic Scaffoldsmentioning
confidence: 99%